Molecular Histopathology and Cytopathology (IntechOpen, 2023)
Various histopathological and cytopathological processes, such as inflammation, cell injury, tissue regeneration, hemodynamic disorders, and neoplasia, constitute important processes in the formation mechanism of many diseases. Molecular mechanisms are involved in the emergence of these basic pathological processes. Learning the organization from molecule to tissue guides investigating the mechanisms of many diseases. This book describes and discusses these pathological processes and their association with molecular mechanisms of the formation of various diseases.